2019
DOI: 10.1111/jan.14244
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional collaboration during medical emergencies among doctors, nurses, and respiratory therapists in the intensive care unit: A phenomenological study protocol

Abstract: Aim:The aim of this study was to explore the lived experiences of interprofessional collaboration among nurses, doctors, and respiratory therapists during medical emergencies in the intensive care unit. Design: Descriptive phenomenological study.Method: Participants will be recruited through purposive sampling with maximum variation across the ICUs in a tertiary hospital in Singapore. Guided by data saturation, data collection will include individual semi-structured interviews with ICU nurses, physicians, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…It is also vital to adhere to evidence-based guidelines and protocols to ensure appropriate ventilation support and minimize harm. Regular monitoring and evaluation of patients' response to ventilation, including factors such as oxygenation levels, lung compliance, and other relevant parameters, should be conducted 41 , 42 . Moreover, interdisciplinary collaboration among healthcare teams involving respiratory therapists, critical care specialists, and other knowledgeable professionals is crucial, especially considering the shortage of experienced staff and experts in transport ventilators 41 , 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also vital to adhere to evidence-based guidelines and protocols to ensure appropriate ventilation support and minimize harm. Regular monitoring and evaluation of patients' response to ventilation, including factors such as oxygenation levels, lung compliance, and other relevant parameters, should be conducted 41 , 42 . Moreover, interdisciplinary collaboration among healthcare teams involving respiratory therapists, critical care specialists, and other knowledgeable professionals is crucial, especially considering the shortage of experienced staff and experts in transport ventilators 41 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Regular monitoring and evaluation of patients' response to ventilation, including factors such as oxygenation levels, lung compliance, and other relevant parameters, should be conducted 41 , 42 . Moreover, interdisciplinary collaboration among healthcare teams involving respiratory therapists, critical care specialists, and other knowledgeable professionals is crucial, especially considering the shortage of experienced staff and experts in transport ventilators 41 , 43 . By implementing these measures, clinicians can increase the optimal use of ventilators, ultimately leading to improved patient survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…While several phenomenological approaches to data analysis exist (Phillips‐Pula et al, 2011), we applied that of Colaizzi's (1978) which is used in nursing and interprofessional research (Liang et al, 2020; Lin et al, 2020; Sheng et al, 2020; Wirihana et al, 2018) and found to be a rigorous and robust approach that ensures credibility and reliability of its results (Wirihana et al, 2018). Colaizzi's (1978) approach involves (i) reading of the interview transcripts several times while listening to the tape recordings; (ii) extracting essential elements and meaningful statements from the transcripts; (iii) coding the same elements and statements of the data; (iv) arranging the formulated meanings into several clusters of themes; (v) ensuring that detailed descriptions were stated and merged for every extracted theme; (vi) undertaking a repeated reading by the researchers of the themes and the descriptions; (vii) returning the data to the participants to obtain their views and to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…While several phenomenological approaches to data analysis exist (Phillips-Pula et al, 2011), we applied that of Colaizzi's (1978) which is used in nursing and interprofessional research (Liang et al, 2020;Lin et al, 2020;Sheng et al, 2020;Wirihana et al, 2018) and found to be a rigorous and robust approach that ensures credibility and reliability of its results (Wirihana et al, 2018). Colaizzi's (1978…”
Section: Discussionmentioning
confidence: 99%
“…The full details of this study design are published in our study protocol (Lin et al, 2020). The following sections will recap the study design and elements.…”
Section: The S Tudymentioning
confidence: 99%